2022
DOI: 10.1097/01.asw.0000823980.15166.35
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adjustment to Living with an Ostomy: Results of a Cross-sectional Study

Abstract: Objective To describe predictors of adjustment to living with an ostomy among Italian adults with an enterostomy or a colostomy. Methods A multicenter, cross-sectional design was performed, sampling 403 patients with an ostomy in three different outpatient clinics of northern Italy between April 2018 and December 2020. Data were collected by stoma therapists in ambulatory settings using the Italian version of the Ostomy Adjustment Inventory-23 and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(96 reference statements)
2
7
0
Order By: Relevance
“…Our findings regarding non‐improvement in quality of life are similar to those of other studies, in which being younger and being female are risk factors for the deterioration or non‐improvement of perceived quality of life 37 . Women reported lower quality of life scores than men, which may be accounted for by the fact that physical and psychological concerns differ greatly between women and men.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings regarding non‐improvement in quality of life are similar to those of other studies, in which being younger and being female are risk factors for the deterioration or non‐improvement of perceived quality of life 37 . Women reported lower quality of life scores than men, which may be accounted for by the fact that physical and psychological concerns differ greatly between women and men.…”
Section: Discussionsupporting
confidence: 88%
“…22 Our findings regarding non-improvement in quality of life are similar to those of other studies, in which being younger and being female are risk factors for the deterioration or non-improvement of perceived quality of life. 37 Women reported lower quality of life scores than men, which may be accounted for by the fact that physical and psychological concerns differ greatly between women and men. The poorest scores were observed in the personal dimension: patients reported feeling more tired at the first follow-up, they were more worried about pouchrelated issues from day 45 after the ostomy, and they were more concerned about psychosocial aspects 1 year on.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies identified that women are more concerned about their appearance, more diligent in stoma care but demonstrate higher levels of depression and fear than men living with ostomy ( Liao and Qin, 2014 ; Sasaki et al., 2012 ). On the contrary, another study noted that characteristics of ostomy such as leakage, smell and noise could increase negative emotions among men and cause impaired adjustment since cultural dynamics equates power and control to the male body ( Dellafiore et al., 2022 ; Gautam and Poudel, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial, higher level of education and young age were associated with fewer psychosocial problems among stoma patients. 22 This might partly be explained by a more active approach against the caregivers among these groups of patients. Other interesting aspects not covered in this paper are the attitudes of healthcare workers and the influence of expectations and perceptions among stoma nurses and other care providers.…”
Section: Discussionmentioning
confidence: 99%